Clinical Implications of Genetic Admixture in Hispanic Puerto Ricans: Impact on the Pharmacogenetics of CYP2C19 and PON1 - Duconge, Jorge; Escalera, Odalys; Korchela, Mohan; Ruaño, Gualberto (IntechOpen, 2012)
None